Design and Pilot Evaluation of a Cross-Training Curriculum for Intimate Partner Violence Advocates and Peer Recovery Coaches - Stone, Rebecca (Victims & offenders, 2023)
Substance use and intimate partner violence (IPV) co-occur, and experts have called for cross-training of IPV and substance use disorder (SUD) professionals. The purpose of this pilot study was to evaluate a cross-training curriculum for IPV advocates and peer recovery coaches. We used a one group pre-posttest study design to evaluate the efficacy and participant experience of the cross-training. Among IPV advocates, the training was associated with improving skills related to working with individuals with SUD, and improving self-efficacy related to working with survivors of IPV. Among recovery coaches, the training was associated with positive changes in self-efficacy regarding working with survivors of IPV and individuals with SUD. Overall, participants reported high satisfaction with the training. Participants indicated that they most appreciated the opportunity to connect with professionals in the other sector, suggesting that such collaborations may help to increase community capacity to respond to individuals experiencing co-occurring IPV and SUD.